2018
DOI: 10.1242/dev.163568
|View full text |Cite
|
Sign up to set email alerts
|

Neurog3-dependent pancreas dysgenesis causes ectopic pancreas in Hes1 mutant mice

Abstract: Mutations in , a target gene of the Notch signalling pathway, lead to ectopic pancreas by a poorly described mechanism. Here, we use genetic inactivation of combined with lineage tracing and live imaging to reveal an endodermal requirement for Hes1, and show that ectopic pancreas tissue is derived from the dorsal pancreas primordium. RNA-seq analysis of sorted E10.5 and Pdx1-GFP cells suggested that upregulation of endocrine lineage genes in embryos was the major defect and, accordingly, early pancreas morphog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…The molecular determinants of pancreatic heterotopia and the pathogenic mechanisms involved are not well known. Earlier studies suggest that pancreatic heterotopia in mice with mutations in Hes1 was caused by transdifferentiation of the embryonic stomach to pancreatic tissue [6], but a recent study proposes that aberrant morphogenesis of the dorsal pancreas primordium is the underlying mechanism in Hes1 mutant mice [7]. We did not observe changes in Hes1 and Ngn3 (a HES1 target gene) expression in the dorsal pancreas of Gata4KO embryos, suggesting that the heterotopic pancreas observed in Gata4-deficient mice might be independent of Notch signaling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The molecular determinants of pancreatic heterotopia and the pathogenic mechanisms involved are not well known. Earlier studies suggest that pancreatic heterotopia in mice with mutations in Hes1 was caused by transdifferentiation of the embryonic stomach to pancreatic tissue [6], but a recent study proposes that aberrant morphogenesis of the dorsal pancreas primordium is the underlying mechanism in Hes1 mutant mice [7]. We did not observe changes in Hes1 and Ngn3 (a HES1 target gene) expression in the dorsal pancreas of Gata4KO embryos, suggesting that the heterotopic pancreas observed in Gata4-deficient mice might be independent of Notch signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic pancreas has been associated with impaired Notch signaling in mice [5][6][7]. We examined the expression of Hes1, a mediator of Notch signaling, and its downstream Figure S3).…”
Section: Gata4-deficient Gastric Epithelium Expresses Pancreatic Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, initial experiments in our labs have shown that Dll1 (and Hes1) expression exhibits ultradian oscillations in the developing pancreas (data not shown) making this heterogeneity a likely result of catching oscillating cells in their peak phase 46 . We have previously shown that Dll1-deficient E10.5 pancreata are hypoplastic due to reduced proliferation 19,22,28 and initial experiments have shown that E10.5 Dll1 Type 1 and Type 2 mutants, in which both Dll1 and Hes1 oscillations are dampened 47 , also present with pancreatic hypoplasia albeit less severe than in Dll1 −/− and Dll1 ΔFoxa2 mutants (data not shown). Here we found the opposite phenotype in E10.5 Jag1-deficient pancreata, which are hyperplastic, suggesting that Jag1 antagonizes Dll1 function at this stage, possibly by a cis-inhibitory interaction that sequesters a fraction of the available Notch receptors.…”
Section: Discussionmentioning
confidence: 84%
“…Dll1 is involved in the control of early endocrine differentiation 20,22 . Yet, PD patterning is unaffected in Dll1 ΔFoxa2 embryos 19 and the endocrinogenic phenotype of E10.5 Dll1 ΔFoxa2 embryos is much weaker than that of E10.5 Mib1 ΔFoxa2 embryos, in which essentially the entire dorsal bud is converted into glucagon cells 19,28 . Together, these findings show that additional Mib1 substrates, most likely other Notch ligands, are involved in these cell fate decisions.…”
mentioning
confidence: 96%